Famfoodie Sdn Bhd / Auni Syadiyah Kamaluddin - Auni Syadiyah, Kamaluddin (2020)
The business of FamFoodie is about selling a newer version of an MRE type food. The new invention includes not using any water like other MRE and are available in different sizes and portions. Unlike other products, we also offered to make a separate batch of not using any well-known allergy products such as peanuts, dairy and chicken eggs. Our main target for the products we are selling is students, campers or working parents and senior citizens. Amidst the pandemic, it is wise to stock up food in order to not being expose in the open too frequently. Since the product we sold can be stored up to 1 month and with enough portion for the entire family, FamFoodie is very practical in this catastrophic. We also offered to deliver straight to the customers houses and are available online in our websites, social media and other delivery platform such as Shopee and Lazada. Our packages are really light, simple and a 100 percent guaranteed that it will not spill out or the chemical heat does not work or fail to heat the food properly. In this time of pandemic, we are giving our best to satisfy every customer and giving out extra precaution to stay safe and healthy.